Analysis and interpretation of regional geophysical data in the Swayze Greenstone Belt of the superior province, Canada (2020)
The Swayze Greenstone Belt is an Archean granitoid-greenstone terrain located in the central part of the Superior Province in Canada. In this region, a number of geophysical projects have been completed by MERC (Mineral Exploration Research Centre, Laurentian University, Sudbury) using different methods. In addition, the Geological Survey of Canada has collected geophysical data that is publicly available. The main objective of this project consisted in doing an analysis and modelling of public regional gravity and aeromagnetic data of the Swayze Greenstone Belt with the aim of examining the geometry and depth extent of the geological bodies that occur in the area of the belt. Gravity and aeromagnetic data from the Geoscience Data base of the Geological Survey of Canada was used, and the GM-SYS tool extension from Oasis montaj - Educational software edition version 9.8.1 was used for forward modelling of the gravity data. Five models were built, three transverse and two longitudinal to the geological structures. The residual magnetic total field of the SGB and its first vertical derivative were analyzed qualitatively by comparing them with the geological units and main structures of the area. A general perspective of the geometry and depth extent of the formations and groups of the SGB was obtained, being concluded that the Brett Lake Syncline is a tight fold, which changes to an open fold in the western part of the Swayze area. The Woman River Anticline is an open to tight fold. The structures modeled under the Brett Lake Syncline vary in depth between 5 and 9 km, whereas for the structures under the Woman River Anticline vary between 2 and 15 km. The deepest parts in the greenstone rocks are located in the central-southern area of the SGB. Furthermore, it was observed the geometry of the SGB and the surrounding and intruding tonalite-granodiorite plutons form a typical Archean keel-and-dome pattern.